Survival After Second Primary Neoplasms of the Brain or Spinal Cord in Survivors of Childhood Cancer: Results From the British Childhood Cancer Survivor Study - Taylor, Aliki J.; Frobisher, Clare; Ellison, David W.; Reulen, Raoul C.; Winter, David L.; Taylor, Roger E.; Stiller, Charles A.; Lancashire, Emma R.; Tudor, Edward C.G.; Baggott, Christina; May, Shaun; Hawkins, Mike M. (Journal of clinical oncology, 2009)
Survival after brain or spinal cord neoplasms is poor and varies by diagnostic group, age, grade, treatment and pretreatment factors, and location and size of tumor. We carried out a study to investigate survival and factors affecting survival of all diagnostic types of second primary brain or spinal cord neoplasms. The British Childhood Cancer Survivor Study (BCCSS) is a long-term population-based follow-up study of 17,980 5-year survivors of childhood cancer. We used relative survival and multivariate Cox regression analysis to determine 5-year relative survival and factors affecting survival in second primary meningiomas and gliomas that developed in survivors included in the BCCSS. There were 247 second primary brain or spinal cord neoplasms, including 137 meningiomas and 73 gliomas in a young adult population. Five-year relative survival after meningiomas was similar for males (84.0%; 95% CI, 72.6% to 91.1%) and females (81.7%; 95% CI, 69.9% to 89.3%). For gliomas, 5-year relative survival was 19.5% (95% CI, 8.6% to 33.7%) for males and females. Multivariate analysis showed significant heterogeneity by decade of treatment (P = .04), grade (P = .03), and genetic risk (P = .03) for rate of mortality after a meningioma. For gliomas, survival was significantly affected by grade (P < .001). Our results indicate survival is poor after second primary glioma in this young adult population, although survival after second primary meningioma is good. Our study has clinical implications for the surveillance of childhood cancer survivors at risk of developing second primary brain tumors, in particular survivors of childhood acute lymphoblastic leukemia or childhood brain tumors.